New principals' leadership and school culture: a study of three primary schools facing challenging circumstances in Trinidad and Tobago - Lee-Piggott, Rinnelle (2016)
The literature on new principals tends to focus on the challenges of incumbents. However, there is little detailed evidence of the nature of their attempts at reshaping or enhancing school culture, which may be their greatest single professional challenge. A significant number of primary schools in Trinidad and Tobago are currently headed by new principals and concerns have been publicly raised at the national level about these new principals’ fit to schools.